2022
DOI: 10.1002/adem.202200656
|View full text |Cite
|
Sign up to set email alerts
|

4D Metamaterials with Zero Poisson's Ratio, Shape Recovery, and Energy Absorption Features

Abstract: Crashworthiness is the ability of the materials or structures to absorb impact energy through plastic deformations, friction, fracture, shear, bending, and even torsion. [1] Energy absorbers have been extensively used for different applications. The most prevalent applications can be found in the automotive, railway, and aerospace industries. [2,3] It is important to reduce the mortality rate caused by car crashes in the automotive industry. When it comes to passengers' safety, some critical crashworthy elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…After loading, the samples were quickly cooled to 25 °C at a rate of 30°min À1 and kept for 120 s. In Figure 2, the programming steps are presented for both the bilayer and encapsulated PCL-TPU structure in bending mode. After unloading, the amount of shape fixity was calculated by measuring the amount of storage deformation according to Equation (1). A, B, C, and D are the initial height, the amount of deformation, and the height after unloading, and recovery, respectively.…”
Section: Shape Memory Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…After loading, the samples were quickly cooled to 25 °C at a rate of 30°min À1 and kept for 120 s. In Figure 2, the programming steps are presented for both the bilayer and encapsulated PCL-TPU structure in bending mode. After unloading, the amount of shape fixity was calculated by measuring the amount of storage deformation according to Equation (1). A, B, C, and D are the initial height, the amount of deformation, and the height after unloading, and recovery, respectively.…”
Section: Shape Memory Effectmentioning
confidence: 99%
“…Shape‐memory polymers (SMPs), as the widest and most widely utilized shape memory materials (SMMs), are a group of smart materials that can fix a temporary shape and can return to its original shape by applying proper stimulation. [ 1 ] In recent years, the 3D printing of SMPs has led to the emergence of the 4D printing term, which was first introduced by Skylar Tibbits. [ 2 ] 4D printing has attracted the attention of researchers because of its benefits and features.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to reassemble simple components into a complex structure that cannot be built with existing manufacturing technologies is a notable case of the design flexibility enabled by 4D printing. Robots [3], automobiles [4], healthcare [5], and aerospace [6] are just some of the emerging markets for three-dimensional (3D) printing technologies, and there has also been a notable shift towards using 4D printing technology to create soft robotics for use in a multitude of environments. The field of soft robotics is a relatively new area of study, with much of the current research being inspired by the systems in nature that have been modified over generations to achieve a certain purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed that by increasing the thickness of structures, although the mass is increased, the energy absorption rate becomes much more considerable, enhancing the SEA. Recently, Hamzehie [ 29 ] introduced zero Poisson's ratio hard meta‐materials with reversible energy‐absorbing features fabricated by 4D printing technology. The deformation could be recovered by simply heating.…”
Section: Introductionmentioning
confidence: 99%